trans-Hydroboration–oxidation products in Δ5-steroids via a hydroboration-retro-hydroboration mechanism - Hilario-Martínez, JC; Murillo, F; García-Méndez, J; Dzib, E; Sandoval-Ramírez, J; Muñoz-Hernández, MÁ; Bernès, S; Kürti, L; Duarte Gonzalez, FJ; Merino, G; Fernández-Herrera, MA (Royal Society of Chemistry, 2020)
Herein, we report for the first time a “trans-hydroboration–oxidation product” isolated and characterized under traditional hydroboration–oxidation conditions using cholesterol and diosgenin as substrates. These substrates are excellent starting materials because of the rigidity and different structural environments around the double bond. Further investigations based on experimental evidence, in conjunction with theoretical studies, indicate that the formation of this trans-species occurs via a retro-hydroboration of the major product to generate the corresponding Δ6-structure and the subsequent hydroboration by the β-face. Besides, the corresponding Markovnikov type products have been isolated in synthetically useful yields. The behavior of the reaction under a range of temperatures is also investigated.